Peningkatan Kapasitas Guru Paud di Kecamatan Leihitu Barat Kabupaten Maluku Tengah - Tutupary, Rosmaryn; Abarua, Hermalina; Abednego, Abednego; Sahalessy, Arnold; Lokollo, Lamberthus Johannes; Amorsea, Rahma; Indah, Wa Ode; Sahetapy, Lisa Maarce; Kundre, Junita Liliana; Noya, Ferdinanda Sherly S (Jurnal Pengabdian Arumbai, 2024)
Improving the capacity of early childhood education (PAUD) teachers in Leihitu Barat District is a strategic step towards enhancing the quality of early childhood education in the region. This study aims to enhance teachers' understanding of the eight accreditation standards set by the government through continuous training and mentoring programs. The methods applied include interactive training, workshops, and direct mentoring by experts. The program's results indicate an increase in teachers' competencies in implementing play-based and contextual learning approaches that are relevant to children's developmental needs. Additionally, collaboration with external institutions, such as universities and local communities, has enriched the training content and expanded access to educational resources. This program is expected to continue as a sustainable effort to ensure that accreditation standards are met and to improve the quality of early childhood education